Prevalence of Malaria Parasites among Pregnant Women and Children under Five years in Ekiti State, Southwest Nigeria. - Iyabo Adepeju SIMON-OKE; M.F Ogunseem; O.J Afolabi; Oluwaseun Awosolu (Journal of Biomedicine and Translational Research, 2019)
Background: Malaria is a deadly disease causing serious public health issues among pregnant women and children worldwide especially in tropical and subtropical Africa. This study was carried out to determine the prevalence of malaria parasites among pregnant women and children under five years in Ekiti State, Nigeria.Methodology: A total of 380 blood samples were collected from the pregnant women and children under five years respectively. Malaria parasites were examined microscopically on thick and thin blood smear stained with Giemsa stain while personal data were collected through questionnaire and confirmed from file records. Red cell phenotyping was carried out manually with standard tube technique for blood group. Haemoglobin electrophoresis was carried out using the cellulose acetate alkaline haemoglobin electrophoresis technique, which allowed for the separation of haemoglobin A, F, S, and C into distinct bands.Results: The results showed that of 380 pregnant women sampled, 153 (40.2%) were positive for malaria parasites and 63 (63%) were positive of the 100 children sampled. The highest prevalence of malaria parasites 18 (51.4%) and 25 (71.4%) were observed in ages 36-39 and <1 years for pregnant women and children respectively. Multigravidae was 1.19 times (95% Cl: 0.77, 1.84) more vulnerable to malaria compare to primigravidae. Women in the first trimester were more infected with malaria parasites 40 (75.4%) than those in second trimester 46 (23.3%) and third trimester 67 (51.9%). Among children under five years of age, females 38 (66.7%) had the highest prevalence compared to males 25 (58.1%). However, there was no significant difference. Statistical analysis showed a significant difference in genotype types (P<0.05).Conclusion: This study revealed that malaria infection is still endemic in the study area, hence, there is urgent need to deploy management strategy to the study area.